A multicentre open‐label study of apremilast in palmoplantar pustulosis (APLANTUS). (24th June 2021) - Wilsmann‐Theis, D.; Kromer, C.; Gerdes, S.; Linker, C.; Magnolo, N.; Sabat, R.; Reich, K.; Mössner, R.
Abstract: Background: Palmoplantar pustulosis (PPP) is a chronic skin disease with painful erythematous scaly or crusty lesions and pustules on the palms and soles. Apremilast is a phosphodiesterase 4 inhibitor that has proven effective in the therapy of psoriasis, psoriatic arthritis and in oral ulcers associated with Behcet's disease. Objective: To explore the efficacy of apremilast in PPP. Methods: APLANTUS was a phase 2 single‐arm multicentre study of apremilast in 21 subjects with moderate‐to‐severe PPP. Primary endpoint was the per cent change of the Palmoplantar Pustulosis Psoriasis Area and Severity Index (PPPASI) at week 20 compared to baseline. Results: 20 weeks of oral treatment with apremilast in patients with moderate‐to‐severe PPP resulted in a significant decrease of the PPPASI with a median reduction of 57.1% (p < 0.001), and 61.9% of patients achieved at least a 50% improvement of the PPPASI relative to baseline. The total number of pustules per patient decreased significantly relative to baseline with 76.2% of patients achieving at least a 50% reduction in total pustules count at week 20. Improvement of PPP was also apparent in a significant decrease of the dermatologic life quality index (DLQI). The median DLQI score dropped from 8.5 at baseline to 2.0 at week 20 (p = 0.030). Apremilast was generally well tolerated, and no serious adverse events occurred. Conclusions: Patients with PPP treated with apremilast showed benefit both in objective and subjective disease parameters. Apremilast should be investigated further in this difficult‐to‐treat skin condition. EudraCT number: 2016‐005122‐11.